Hybrid structures for Achilles' tendon repair. (15th April 2022) - Peixoto, Tânia; Carneiro, Sofia; Pereira, Fábio; Santos, Cristóvão; Fangueiro, Raúl; Duarte, Isabel; Paiva, Maria C.; Lopes, Maria A.; Guedes, Rui M.
Abstract: The management of extensive tendon injuries poses a considerable challenge. These cases typically require a partial replacement of the tissue, and conventional treatment options, either grafts or synthetic constructs, present disadvantages. Synthetic constructs may be produced with either non‐biodegradable or biodegradable polymers. However, while the former lacks biointegration, the latter requires a compromise between tissue ingrowth and biodegradability, frequently malfunctioning due to inadequate mechanical properties. The present work presents a textile medical device designed to repair the Achilles tendon (AT). This device is based on a core/shell design that mimics the multiscale organization of the native tissue. The core comprises several hybrid braids based on poly(ethylene terephthalate) (PET) and poly(lactic acid) (PLA) yarns, and the shell consists on braided PET yarns surrounding the core. Different PET/PLA compositions of the core braids were studied to optimize biodegradability without compromising mechanical performance. The morphology and mechanical properties of the structures were studied. The hybrid structures presented a non‐linear force–strain curve comparable to a representative curve described for a native tendon. A decrease in force and stiffness was observed as the PLA content in the structure increased. Nevertheless, the obtained values for the hybrid structures are promising for AT replacement. Besides, these hybrid structures demonstrated appropriate resistance to cyclic loading and a beneficial creep behavior. The results obtained in the present work fall within the range of values reported for the native AT.